Training translators - Gurdial Singh, K.K. (2011)
The researcher undertook a study of the process of translating scientific texts from English to Malay in Malaysia. Her objective was to find out the processes involved in the translation process and therefore, what instructors should know when teaching translation students who wish to practice translating in the real world. The methodology comprised both quantitative and qualitative methods i.e. a questionnaire, interviews and think-aloud protocols. This study only looked into the process of translating and not the product. Her participants comprised fifty part-time translators who took part in a questionnaire and five part-time translators of scientific texts who took part in the interviews and think-aloud protocols. Based on the results of this study, the researcher believes that in training translators, an instructor should teach the basic theories of translation, processes, steps, approaches, and strategies involved while translating, and how to go about managing terminology. This paper presents the findings from this study and also discusses the researcher's proposed translation model which can be used as a guide for training translators.